The Effects of Preoperative Endoscopic Tattooing on Distal Surgical Margin and Ileostomy Rates in Laparoscopic Rectal Cancer Surgery: A Prospective Randomized Study. Issue 4 (August 2016) - Cipe, Gokhan; Cengiz, Merve B.; Idiz, Ufuk O.; Yardimci, Erkan; Malya, Umit; Firat, Deniz; Muslumanoglu, Mahmut
Abstract : Aim: This study aimed to evaluate the effect of endoscopic marking on the distal surgical margin and ileostomy rates in laparoscopic rectal cancer surgery. Materials and Methods: Forty patients, who underwent surgery between September 2012 and December 2013 for rectal cancer limited to or with invasion of the upper rectum, were included in the study. The distal tumor margin was marked with purified carbon particles by colonoscopy before surgery in one group (n=20); no marking was performed in the second group (n=20). Patients were assigned randomly to each group. Laparoscopic anterior or low-anterior resection was performed in all patients. Demographic and operative data, pathology results, morbidity, and ileostomy rates were measured. Results: There was no statistically significant difference in the demographic data, the tumor size, the amount of bleeding, the specimen length, the harvested lymph node number, postoperative complications, the length of hospital stay, rehospitalization, and the operation duration between groups 1 and 2, respectively. The distal surgical margin was significantly shorter in the marked group. The protective ileostomy rates were also lower in the marked group; however, the difference did not reach statistical significance. Conclusions: Preoperative endoscopic tattooing decreases distal resection margins and may reduce protective ileostomy rates in laparoscopic rectal surgery.